A subharmonic mixer for the 220–325 GHz frequency range - Zorenko, A.V.; Kolesnik, N.V.; Kritskaya, T.V.; Kudryk, Ya.Ya.; Marunenko, Yu.V.; Ryzhanovich, L.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2013)
We have made a subharmonic mixer (SHM) for the 220–325 GHz frequency range with conversion losses lower than 30 dB at the intermediate frequency 3 GHz. The subharmonic mixer design was based on a GaAs mixer Schottky barrier diode with beam leads on a quartz 25-μm thick microwave board. The microwave board was placed in a package with a waveguide channel of local oscillator input (cross-sectional area 1.2×2.4 mm) and waveguide channel of signal input (cross-sectional area 0.4×0.8 mm² ). The IF signal goes out through a subminiature A-connector, wave impedance of which is 50 Ohm.